Fruit traceability via mobile application - Reffatti, Leonardo; Gonçalves de Oliveira, Guilherme; Shibata, Marília (Comunicata Scientiae, 2021)
The traceability of agricultural products is essential to guarantee food security, monitor the production chain and is a requirement of Brazilian legislation. The optimization of this activity can be performed with the use of digital technologies. The present study verified the efficiency of a mobile app to track agricultural products and use it as a digital field book. The study was developed with 13 participants who used the mobile app to record agricultural activities: input pesticide sprays and fertilization; cultural management and registration of georeferenced harvest lots. The use of the app simplified the registration of tasks as digital field book and tracked agricultural products throughout the productive chain. An alert system for withholding period and maximum limit for pesticide sprays had been developed and enabled greater control, both are considered critical points in traceability system. QR-code of fruit lots were produced in each harvest and reports of costs, production, yield and fruit quality were generated by the app. Thus, mobile app was efficient to track agricultural production and use it as digital field book. In addition, managing of agricultural activities and production costs were produced and it has been shown that an innovative and low-cost technology that can be used by fruit producers.